2013
DOI: 10.1039/c3cp53027b
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation of ethanol and 2-propanol on TiO2(110): evidence for methyl radical ejection

Abstract: The photooxidation of ethanol and 2-propanol was studied under UHV conditions on a single crystal TiO2(110) surface using a combination of temperature programmed desorption (TPD) and pump-probe laser ionization techniques. Previous studies of these reactions have shown that the first step involves photocatalytic dehydrogenation to either an acetaldehyde or acetone intermediate. In this work, we show that when adsorbed alcohols are irradiated with UV light in the presence of molecular oxygen, methyl radicals ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 49 publications
5
28
0
Order By: Relevance
“…In surface science, where single crystalline surfaces can be studied at ultrahigh vacuum (UHV) conditions, particular focus has been on the interaction between EtOH and the rutile TiO 2 (110)–(1 × 1) surface 27 28 29 30 31 32 33 34 35 36 37 38 39 , because this surface is the most stable one of rutile and often serves as a model for transition metal surfaces 1 2 3 4 10 11 12 . The TiO 2 (110)–(1 × 1) surface consists of alternating rows of fivefold-coordinated titanium (5f-Ti) atoms (the Ti troughs) and protruding, twofold coordinated bridge-bonded oxygen (O br ) atoms.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In surface science, where single crystalline surfaces can be studied at ultrahigh vacuum (UHV) conditions, particular focus has been on the interaction between EtOH and the rutile TiO 2 (110)–(1 × 1) surface 27 28 29 30 31 32 33 34 35 36 37 38 39 , because this surface is the most stable one of rutile and often serves as a model for transition metal surfaces 1 2 3 4 10 11 12 . The TiO 2 (110)–(1 × 1) surface consists of alternating rows of fivefold-coordinated titanium (5f-Ti) atoms (the Ti troughs) and protruding, twofold coordinated bridge-bonded oxygen (O br ) atoms.…”
mentioning
confidence: 99%
“…The adsorption of EtOH and the thermally activated chemistry of EtOH on rutile TiO 2 (110)–(1 × 1) have been studied previously by means of photoelectron spectroscopy (PES) 28 30 44 , temperature-programmed desorption (TPD) 27 28 29 32 33 36 37 38 39 , femtosecond two-photon photoemission spectroscopy (2PPE) 36 , and scanning tunnelling microscopy (STM) 32 33 35 . In addition, the EtOH–TiO 2 (110) interaction has been studied using density functional theory (DFT) calculations 31 32 33 34 35 36 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Not only O−H bond scission, C−C bond can also be broken during the photo-irradiation. Recent results obtained by Kershis and coworkers [17] using temperature programed desorption (TPD) and pump-probe laser ionization techniques have shown that methyl radicals are produced during the photocatalytic oxidation of 2-propanol on R-TiO 2 (110). The result showed that the first step involves photocatalytic dehydrogenation to acetone intermediate, similar to previous studies [7,10,11].…”
Section: Introductionmentioning
confidence: 99%